From Chalipate to Modern State: A Reflection of Ibn Khaldun's Thought - Mohammad Zainor Ridho (Ulumuna, 2019)
Ibn Khaldun is one of the great scholars in the fields of sociology, history, philosophy, religion and politics. His thoughts are illuminating to scholars both in the East and the West. This study aims to examine this Muslim scholar’s thought on Islamic government and political system. Based on a critical-textual analysis of his work, this study shows that Ibn Khaldun formulates caliphate as general leadership of all Muslims in the world and is aimed at upholding shari’a law and spreading Islamic propagation and functions both for handling religious and worldly political affairs. The philosophical and historical analysis shows that the caliphate emerged upon the death of the Prophet and the ideal system of the caliphate lasted in the four righly-guided of the Prophet’s successors. In the subsequent periods, the Islamic leadership theories and practices vary accordingly, ranging from caliphate to imamate. Nowadays, there is a call to return to the caliphate system but, as this study argues, in the Ibn Khaldun practical-realistic theory, such a call is hardly fulfilled due to irreconcilable political system and different socio-religious contexts between those ideal periods and those of the current challenges.